SHARED UNDERSTANDING ON THE CONCEPT OF ENTREPRENEURSHIP EDUCATION BY TEACHERS AND BUSINESSMEN / THE CONCEPT OF ENTREPRENEURSHIP EDUCATION IN LITHUANIAN SCHOOLS SHARED BY TEACHERS AND BUSINESSMEN - Žibėnienė, Gintautė; Virbalienė, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article highlights the importance of entrepreneurship education in a modern day educational institution. Strategic documents of the EU invite the educational institutions to cooperate more actively with the business world in order to have the best quality entrepreneurship education. So the main aim of the research is to determine the concept of entrepreneurship shared by teachers and businessmen. Firstly, the concept of entrepreneurship and its development is reviewed, taking into account the legislations and scientist observations. The second part of the article presents the similarities and differences on the concept of entrepreneurship from the point of view of teachers and businessmen. These differences can suggest what relevant aspects, indicated by the representatives of the business world, could be included into the process of organization of the entrepreneurship education and to improve.